The Wizard of Tuskegee Trapped Us, Historical Materialism May Free Us: A Response to Zine Magubane's Coss Dialogue Lecture. - Tunstall, Dwayne A. (Pluralist)
The article responds to Dr. Zine Magubane's lecture by critiquing Booker T. Washington's racial accommodationism, critical race theory (CRT), and US-centric sociology of race. Magubane argues that Washington's ideology served as a cover for capitalist structures, emphasizing class over race in understanding societal relations. She advocates for a historical materialist approach to study social relations, focusing on class-based accounts rather than race-based ones. The article raises concerns about the limitations of race-based analyses and the need for a comprehensive understanding of social inequalities in the US.